EFFECTIVE AND INEFFECTIVE STRATEGIES FOR INTRODUCING NEW TECHNOLOGY AND IMPLEMENTING CHANGE IN SCHOOLS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The integration of technology in education is a transformative process that can greatly enhance teaching and learning outcomes. However, the success of implementing technological changes in schools heavily depends on the methods and strategies employed. This paper explores both the effective ("good") and ineffective ("bad") approaches to bringing new technology into schools, focusing on key factors such as stakeholder involvement, planning, training, infrastructure, resistance to change, and sustainability